Testing in the pedagogical control of technical readiness of football player's. - Doroshenko E.Iu; Shalfeev P.A (Kharkov National Pedagogical University, 2012)
Application of testing for pedagogical control of technical readiness of footballers during the annual cycle of preparation is considered. 48 sportsmen took part in an experiment. The followings tests are applied: on a technique and accuracy of blow to the gate, on quality of dribbling and special speed with the attack of gate, on quality of dribbling and special speed. It is rotined that the resulted list of exercises is effective enough for determination of level of technical readiness of footballers. It is set that in the structure of annual cycle of preparation specific facilities of testing are the necessary component of pedagogical control of level of technical readiness of footballers. It is recommended for the optimum estimation of level of technical readiness of footballers to choose exercises which represent the level of implementation of concrete elements of technique most adequately. The analysis of testing results testifies to the presence of tendencies to more high indexes speed-power to the orientation in a senior group, that, probably, contingently age-dependent divergences and higher indexes of physical development.